Discriminating Natal Source Populations of a Temperate Marine Fish Using Larval Otolith Chemistry - Rogers, Troy A.; Fowler, Anthony J.; Steer, Michael A.; Gillanders, Bronwyn M. (Frontiers in Marine Science, 2019)
The life cycles of many marine species depend on a dispersive larval stage that connects spatially segregated populations. However, quantifying larval movement among populations remains one of the greatest challenges in marine ecology. Such movement determines whether a population is essentially a self-recruiting stock, or if it forms part of a larger meta-population where recruits originate from multiple sources. Previous research has struggled to differentiate between such stock structure models for King George whiting (Sillaginodes punctatus; Perciformes) in southern Australia, largely due to difficulties in identifying the source populations of dispersing larvae. In this study, pelagic larvae were collected throughout the only recognized spawning area in South Australia in 2017 and 2018. First, we identified that the distribution of larvae was broadly divisible into two groups – those in southern Spencer Gulf and those in Investigator Strait. Then, the incremental structure and elemental composition of otoliths of larvae from the two regions were compared to determine if they had originated from a common source population. There were no spatial differences in the sizes (3.0-5.0 mm SL), ages (5-21 d), hatch dates (7-24 April) or average growth rates (0.09-0.21 mm d-1) of larvae. However, multi-elemental (Li, Mg, Mn, Sr and Ba) otolith signatures differed significantly between the two regions, primarily driven by differences in concentrations of Li and Ba. Although otolith signatures were year-specific, larvae were assigned to their region of capture with 70-82% accuracy. Larvae in each region hatched at the same time yet had significantly different otolith chemistry, providing strong evidence that those in southern Spencer Gulf and Investigator Strait originated from spatially segregated water masses. This study has demonstrated the ability of otolith chemistry to discriminate source populations of pelagic larvae in a fully marine environment, which provides a basis to quantify larval movement between fish populations.